Comparative Evaluation of Low-Cost LiDAR and Ultrasonic Sensors for River Level Monitoring - Kupper, Klaus Dieter; Sausen, Jordan Passinato; Campos, Mauricio de (Anais do Workshop de Computação Aplicada à Gestão do Meio Ambiente e Recursos Naturais (WCAMA), 2026)
Flood monitoring in data-scarce tributaries remains limited by the high cost of conventional hydrometric infrastructure. This paper presents a comparative evaluation of three low-cost non-contact sensors, two LiDAR and one ultrasonic, for river level measurement, validated through controlled laboratory tests and real-world bridge deployments under contrasting weather conditions. Results reveal three key findings: (1) direct solar radiation reduces LiDAR availability by up to 67%, with severity depending on sensor design; (2) wide-angle line-beam optics provide up to 8× improvement in measurement stability over dynamic water surfaces compared to narrow spot-beam configurations; and (3) water turbidity confirms improved LiDAR accuracy. ISO 4373:2022 benchmarking shows that the ultrasonic sensor achieves consistent availability across conditions, while LiDAR sensors require careful design-level selection based on deployment environment.